Strategie e strumenti di valutazione formativa per promuovere l'apprendimento autoregolato: una rassegna ragionata delle ricerche empiriche - Irene Dora Maria Scierri (LED Edizioni Universitarie, 2021)
The area of research into the relationship between formative assessment and self-regulated learning is well established. Several studies have explored the connection between assessment and self-regulated learning, but the literature shows that there are still several lines of research to be explored, including examining which formative assessment practices actually help students improve their self-regulation skills and under which conditions. The paper presents a reasoned review of empirical studies, with experimental or quasi-experimental research design, that have examined the effect of formative assessment practices on self-regulated learning. The target population includes students from all levels of education. It was possible to classify two different ways of implementing formative assessment practices: a global approach and an analytical approach. Most of the reviewed studies recorded significant positive effects on self-regulation. The results and implications for future research are discussed.